Astragaloside IV Attenuates the Myocardial Injury Caused by Adriamycin by Inhibiting Autophagy - Luo, Li-Fei; Qin, Lu-Yun; Wang, Jian-Xin; Guan, Peng; Wang, Na; Ji, En-Sheng (Frontiers in Pharmacology, 2021)
Astragaloside IV (ASIV) is the main active component of Astragalus, which can improve cardiomyocyte hypertrophy, apoptosis and fibrosis. In this experiment, we studied how ASIV reduces the cardiotoxicity caused by adriamycin and protects the heart. To do this, rats were divided randomly into control, ADR, ADR+ASIV and ASIV group (n=6). Echocardiography is used to evaluate cardiac function, HE staining to observe myocardial injury, TUNEL staining to observe myocardial cell apoptosis, and then immunofluorescence and western blotting to observe the expression of related proteins. Experiments have found that adriamycin can damage rat heart function, increase rat cell apoptosis index, autophagy level and oxidative stress level. The further results showed that ADR could inhibit the activity of PI3K/Akt pathway. ASIV treatment can significantly improve the cardiac function of ADR rats and regulate autophagy, oxidative stress and apoptosis. Our findings indicate that ASIV may reduce heart damage caused by adriamycin through activating the PI3K/Akt pathway.